English /v/ Under Pressure: Phonological Interference among Kaili Rai EFL Students - Adinda Mawadda Rahma; Siska Bochari; Mukrim Mukrim; Nursehang Thamrin (MASI Mandiri Edukasi, 2026)
This study investigates phonological interference in the production of the English voiced labiodental fricative /v/ among Kaili Rai EFL students. The research problem arises from the frequent substitution of /v/ with /f/ among Indonesian learners, while variation across phonological positions and specific regional language backgrounds remains underexplored. The objective of this study is to identify the types and frequency of interference in /v/ pronunciation and to examine positional vulnerability in its realization. A descriptive quantitative design was employed. Thirty-four students were selected through purposive sampling from a population of 211. Data were gathered using word lists, minimal pairs, and sentence reading tasks containing /v/ in initial, medial, and final positions. The recordings were transcribed using the International Phonetic Alphabet (IPA) and analyzed through frequency and percentage calculations. The findings reveal three types of interference: substitution, omission, and epenthesis, with substitution emerging as the most dominant pattern. Interference occurred more frequently in word-initial and word-final positions than in medial positions, indicating that phonological position plays a significant role in second language segment production. The results demonstrate that pronunciation difficulty is not solely caused by the absence of a phoneme in the first language but is also shaped by positional distribution.